Genome-wide comparative analyses of GATA transcription factors among 19 Arabidopsis ecotype genomes: Intraspecific characteristics of GATA transcription factors. - Mangi Kim (PLoS ONE, 2021)
GATA transcription factors (TFs) are widespread eukaryotic regulators whose DNA-binding domain is a class IV zinc finger motif (CX2CX17-20CX2C) followed by a basic region. Due to the low cost of genome sequencing, multiple strains of specific species have been sequenced: e.g., number of plant genomes in the Plant Genome Database (http://www.plantgenome.info/) is 2,174 originated from 713 plant species. Thus, we investigated GATA TFs of 19 Arabidopsis thaliana genome-widely to understand intraspecific features of Arabidopsis GATA TFs with the pipeline of GATA database (http://gata.genefamily.info/). Numbers of GATA genes and GATA TFs of each A. thaliana genome range from 29 to 30 and from 39 to 42, respectively. Four cases of different pattern of alternative splicing forms of GATA genes among 19 A. thaliana genomes are identified. 22 of 2,195 amino acids (1.002%) from the alignment of GATA domain amino acid sequences display variations across 19 ecotype genomes. In addition, maximally four different amino acid sequences per each GATA domain identified in this study indicate that these position-specific amino acid variations may invoke intraspecific functional variations. Among 15 functionally characterized GATA genes, only five GATA genes display variations of amino acids across ecotypes of A. thaliana, implying variations of their biological roles across natural isolates of A. thaliana. PCA results from 28 characteristics of GATA genes display the four groups, same to those defined by the number of GATA genes. Topologies of bootstrapped phylogenetic trees of Arabidopsis chloroplasts and common GATA genes are mostly incongruent. Moreover, no relationship between geographical distribution and their phylogenetic relationships was found. Our results present that intraspecific variations of GATA TFs in A. thaliana are conserved and evolutionarily neutral along with 19 ecotypes, which is congruent to the fact that GATA TFs are one of the main regulators for controlling essential mechanisms, such as seed germination and hypocotyl elongation.